STRATEGI KOMUNIKASI PEMASARAN MELALUI BAHASA IKLAN: STUDI KASUS GREEN HOST HOTEL - Isha Aprinica, Ni Putu; Eka Susanti, Luh; Agung Ayu Arun Suwi Arianty, Anak; Made Yuni Kusumadewi, Ni; Ariel Artha Indrayana, Putu (CV. Lafadz Jaya, 2024)
Marketing is an important aspect in the success of a business, including in the hotel industry. In an effort to promote their products or services, hotels need to develop an effective marketing communications strategy. One strategy that can be used is through advertising language. Green Host Hotel is an example of a hotel that offers an environmentally friendly concept. This concept emphasizes sustainable and environmentally responsible business practices. In an effort to market itself, Green Host hotels use advertising language aimed at target markets who are sensitive to environmental issues and want to stay in environmentally friendly hotels. However, even though the Green Host hotel has adopted a marketing communication strategy through advertising language, there has been no research that specifically examines the effectiveness of this strategy in attracting interest and influencing consumer behavior. Therefore, this research aims to analyze marketing communication strategies through advertising language used by Green Host hotels and identify the extent of the effectiveness of these strategies in influencing consumer perceptions and decisions.